Cultivating democratic literacy through the arts : guiding preservice teachers towards innovative learning spaces in ELA classrooms - Hartman, Pamela; Spanke, Jeff (Advances in teacher education., 2024)
"This edited book includes chapters written by English Language Arts (ELA) teacher educators and practicing secondary teachers who examine their classroom experiences through an arts-based habit of mind. Rather than focusing exclusively on artistic approaches to ELA instruction, these chapters collectively frame the teaching of English Language Arts as an art in itself. As such, the arts-informed habits of mind discussed in this book refer more to sets of artistic dispositions than pedagogical methods. In their unique ways, each of these chapters argue that aesthetically charged ways of thinking allow preservice and practicing teachers to develop critical and creative thinking skills and to purposely communicate, to recognize that individual beliefs and values are influenced by personal and social factors, and to set goals for their own learning as well as the learning of their future students' learning. Specifically, in this book, experts in their fields illustrate the power of cultivating artistic-infused dispositions and projects that promote these habits of mind and discuss how these approaches promote literacy instruction in their respective curricula"--